ASSESSING THE EXTERNAL OR INTERNAL USE OF VIDANG CHURNA (EMBELIA RIBES POWDER) IN TREATMENT AND PREVENTION FROM OBESITY AND COMORBIDITY - Abhilasha; Savanur, Prasanna V. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aims to evaluate the efficacy of vidang churna (Embelia ribes powder) both in its internal and external applications. The investigation seeks not only to substantiate traditional claims made regarding this herbal formulation but also to provide a contemporary evidence-based understanding of its potential benefits as supported by recent scientific inquiries. The methodology employed in this research involved a systematic literature review alongside clinical surveys conducted among practitioners who utilize this formulation in their therapeutic regimens. The findings of the research elucidate significant correlations between the administration of vidang churna and reduced body mass index (BMI), along with improvements in metabolic markers such as triglycerides and cholesterol levels. Participants reported marked benefits observed over a treatment duration of various lengths, revealing consistent patterns of weight management and a decline in obesity-related complications such as hypertension and type 2 diabetes. This investigation is particularly original in its holistic approach, integrating both classical Ayurvedic perspectives and modern scientific analyses to evaluate the versatility of vidang churna. The originality of this study lies in its synthesis of traditional knowledge with contemporary research methodologies, establishing a foundation for future guided explorations of polyherbal formulations in weight management practices. Implications stemming from this analysis extend far beyond academia, offering significant contributions to clinical practices concerning weight management and preventive healthcare strategies. By validating the historical uses of vidang churna through empirical evidence, the study advocates for its integration into dietary interventions and therapeutic regimes aimed at obesity treatment.